2009
DOI: 10.1111/j.1365-2842.2009.02003.x
|View full text |Cite
|
Sign up to set email alerts
|

Colour compatibility between teeth and dental shade guides in Quinquagenarians and Septuagenarians

Abstract: The aim of this investigation was to determine colour compatibility between dental shade guides, namely, VITA Classical (VC) and VITA 3D-Master (3D), and human teeth in quinquagenarians and septuagenarians. Tooth colour, described in terms of L*a*b* values of the middle third of facial tooth surface of 1391 teeth, was measured using VITA Easyshade in 195 subjects (48% female). These were compared with the colours (L*a*b* values) of the shade tabs of VC and 3D. The mean coverage error and the percentage of toot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 20 publications
2
51
0
Order By: Relevance
“…It was, furthermore, confirmed that, in comparison with the VC, the 3D was extended toward yellow-red hues and more saturation [6]. In agreement with this finding, several studies of different population groups found that coverage of human tooth colors is better with the 3D than with the VC [7,8], although coverage by the 3D is not satisfactory for a small percentage of human tooth colors [6,9,10]. It has also been confirmed that the tabs of 3D are more ordered and more uniformly spaced than the tabs in traditional shade guides, although a genuinely uniform interval, on the basis of the color axes, between adjacent tabs could not be achieved [11].…”
Section: Introductionsupporting
confidence: 77%
“…It was, furthermore, confirmed that, in comparison with the VC, the 3D was extended toward yellow-red hues and more saturation [6]. In agreement with this finding, several studies of different population groups found that coverage of human tooth colors is better with the 3D than with the VC [7,8], although coverage by the 3D is not satisfactory for a small percentage of human tooth colors [6,9,10]. It has also been confirmed that the tabs of 3D are more ordered and more uniformly spaced than the tabs in traditional shade guides, although a genuinely uniform interval, on the basis of the color axes, between adjacent tabs could not be achieved [11].…”
Section: Introductionsupporting
confidence: 77%
“…used the Easyshade (Vita‐Zahnfabrik) spectrophotometer and a minimum age of 18 years for participants. Cocking et al . and Eiffler et al .…”
Section: Discussionmentioning
confidence: 97%
“…This difference might be because the age of 58% of the sample was 21–30 years. Cocking et al . published a minimum L* value of 52.0 units and a maximum L* value of 90.0 units, whereas Zhu et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy has been quantified by calculation of coverage error, the mean value of the minimal color differences amongst each tab in the shade guide and the database of human teeth. 17,[73][74][75][76] Although teeth exhibit color transitions in all directions, the correlation between colors of different regions on the labial tooth surface has been recorded. This study, performed using digital camera, suggested that color of a missing part of a tooth can be determined using the color of existing areas.…”
Section: Color Compatibilitymentioning
confidence: 99%